2019
DOI: 10.1111/anae.14922
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intrathecal bupivacaine/morphine on quality of recovery in robot‐assisted radical prostatectomy: a randomised controlled trial

Abstract: Summary Robot‐assisted radical prostatectomy causes discomfort in the immediate postoperative period. This randomised controlled trial investigated if intrathecal bupivacaine/morphine, in addition to general anaesthesia, could be beneficial for the postoperative quality of recovery. One hundred and fifty‐five patients were randomly allocated to an intervention group that received intrathecal 12.5 mg bupivacaine/300 μg morphine (20% dose reduction in patients > 75 years) or a control group receiving a subcutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 22 publications
4
40
0
Order By: Relevance
“…Our ITMB data are similar to those of previous laparoscopic and open surgery reports [ 5 , 22 24 ]; thus, ITMB is a feasible and practicable form of pain relief (yielding a lower pain score and lower opioid requirement). Moreover, it was not associated with serious complications (such as nerve injury) during or after surgery, and was better than RSB or IV-PCA alone.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our ITMB data are similar to those of previous laparoscopic and open surgery reports [ 5 , 22 24 ]; thus, ITMB is a feasible and practicable form of pain relief (yielding a lower pain score and lower opioid requirement). Moreover, it was not associated with serious complications (such as nerve injury) during or after surgery, and was better than RSB or IV-PCA alone.…”
Section: Discussionsupporting
confidence: 88%
“…This pain arises from skin-port incisions, multiple dissections of prostate-involved and surrounding tissues, bladder spasm, and transurethral catheter irritation [ 4 ]. Various central and/or peripheral pain-relief methods have been used to attenuate the severe pain that develops immediately after RALP [ 5 , 6 ]. A rectus sheath block (RSB) regimen affords peri-umbilical incision site analgesia superior to that achieved via local anesthetic infiltration; this site is the principal source of pain immediately after laparoscopy-based surgery [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a gynecological study, the addition of intrathecal bupivacaine to intrathecal morphine signi cantly improved postoperative pain relief, but the addition of rectus sheath bupivacaine to intrathecal morphine did not afford additional analgesia [16]. A urological study suggested that multimodal pain control via intrathecal bupivacaine/morphine may optimally improve the quality of early recovery and reduce postoperative pain, being associated with less pain during exertion and fewer bladder spasms (compared to a control group) [5]. Our ITMB block data are similar to those of previous laparoscopic or open surgery reports [5,[14][15][16]; the ITMB block was a feasible and practicable form of pain relief, not associated with serious complications (such as nerve injury) during or after surgery, and was better than the RSB or IV-PCA alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, RALP patients frequently experience considerable pain, particularly on the day after surgery, re ecting the skin-port incisions, multiple dissections of prostate-involved and surrounding tissues, bladder spasm, and transurethral catheter irritation [4]. Various central and/or peripheral pain-relief methods have been used to attenuate the severe pain that develops immediately after RALP [5,6]. A rectus sheath block (RSB) afforded peri-umbilical incision site analgesia superior to that achieved via local anesthetic in ltration; this site is the principal source of pain immediately after laparoscopy-based surgery [7].…”
Section: Introductionmentioning
confidence: 99%
“…This pain arises from skin-port incisions, multiple dissections of prostate-involved and surrounding tissues, bladder spasm, and transurethral catheter irritation [4]. Various central and/or peripheral pain-relief methods have been used to attenuate the severe pain that develops immediately after RALP [5,6]. A rectus sheath block (RSB) regimen affords peri-umbilical incision site analgesia superior to that achieved via local anesthetic in ltration; this site is the principal source of pain immediately after laparoscopy-based surgery [7].…”
Section: Introductionmentioning
confidence: 99%